Hubungan Riwayat Abortus, Usia Kehamilan dan Kunjungan ANC Dengan Kejadian Berat Badan Lahir Rendah (BBLR) di Wilayah Kerja Puskesmas Tanjung Batu Tahun 2023 - Marpuah, Marpuah; Farida, Tuti; Afrika, Eka; Romadhon, Muhammad (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Low birth weight babies (LBW) are still a problem in the health sector, especially perinatal health. The prevalence of LBW according to WHO in the world is 15 to 20 percent or around 20 million births per year. According to WHO (2020), deaths due to LBW in Indonesia reached 22,362 or 1.32 percent of the total deaths in Indonesia. This makes Indonesia ranked 76 out of 183 countries in the TOP 50 Causes Of Death for cases of death due to LBW (World Health Rankings, 2020). The purpose of this study was to find out the relationship between history of abortion, gestational age and ANC visits simultaneously with the incidence of low birth weight (LBW) in the working area of the Tanjung Batu Health Center in 2023. Type and Design This research is quantitative using an analytic survey method with a cross sectional approach. The population in this study were all newborns in the Tanjung Batu Health Center area in 2022, a total of 427 newborns. The sample used amounted to 81 respondents. Sampling using systematic random techniques. The results of the univariate analysis were obtained from 81 respondents, 14 respondents (17.3%) experienced LBW and 67 respondents (82.7%) did not. The results of the chi-square statistical test for the variable history of abortion obtained ρ value = 0.000, the variable gestational age ρ value = 0.000, and the ANC visit variable ρ value = 0.000 less than α = 0.05 indicating that there is a significant relationship between history of abortion and gestational age and ANC visits with LBW incidents at the Tanjung Batu Health Center in 2023. Suggestions for the leadership of the Tajung Batu Health Center are that it is hoped that this research can be used as a basis for the health center in making policies related to health problems for pregnant women so as to reduce the risk of giving birth to babies with low birth weight